Preoperative Anxiety and Social Support among Patients undergoing Surgery - Sharma, Sharada; Gharti, Kamala (Janapriya Journal of Interdisciplinary Studies, 2019)
Most patients awaiting surgery experience anxiety. The study aims to assess the levels of preoperative anxiety and social support, determine the association of background variables with levels of preoperative anxiety and social support and to examine the relationship between levels of preoperative anxiety with social support. A hospital based cross-sectional study was conducted among patients undergoing surgery in a government Hospital, Pokhara. The study period was from September 2016 to August 2017. Total sample was 442 patients scheduled for surgery. Data was collected through Anxiety Specific to Surgery Questionnaire for anxiety and Multidimensional Scale of Perceived Social Support through face to face interview. Ethical approval was obtained from IRC, Institute of Medicine, Tribhuvan University. Data were entered and analysis was performed with the help of the Statistical Package for Social Science (SPSS).The total 94.1 percent of patients were married and 52 percent had low living standard. High level of preoperative anxiety and social support are seen in 42.1 and 64.3 percent respectively. Preoperative anxiety had significant statistical association with standard of living, experience of past operation, and types of operation(p<0.05). Social support had significant statistical association with age, gender, residence, standard of living, and types of operation (p<0.05). Correlation between preoperative anxiety and social support insignificant (r = -.133, p = 0.005) at the 0.05 level. As social support increased; preoperative anxiety decreased. Therefore, health care provider should identify patients with high anxiety, encourage them to talk about their feelings and facilitate more time with their families.